Efisiensi Energi Jaringan Homogeneous Wcdma/3g Pada Lingkungan Outdoor - Linawati, Linawati; Indra ER, Ngurah; Aries Pratama, IGP. Agus (Majalah Ilmiah Teknologi Elektro; Vol 12 No 1 (2013): (January - June) Majalah Ilmiah Teknologi Elektro, 2013)
Telecommunication technology and applications have developed fast recently. Hence this development will take energy consumption significantly. Many studies have been done on energy efficiency on cellular network. The studies are more focused on energy usage of the base station, as the base station is the component of cellular station which takes the most energy consumption. Therefore this study analyzes energy efficiency on homogeneous network of WCDMA/3G for outdoor environment. Energy consumption of three macro base stations is compared with energy consumption of 12 micro base stations. This comparison analysis has been conducted on the same Area Spectral Efficiency (ASE). The results show that the macro base stations are more efficient for energy usage than the micro base stations. However based on ASE requirements, the micro base stations are more efficient than the macro base stations on both busy hours and non-busy hour.
Keywords: WCDMA, base station, energy efficiency, area spectral efficiency